2023
DOI: 10.1002/lpor.202200308
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Hermitian Control of Topological Scattering Singularities Emerging from Bound States in the Continuum

Abstract: Leveraging topological properties in the response of electromagnetic systems can greatly enhance their potential. Although the investigation of singularity‐based electromagnetics and non‐Hermitian electronics has considerably increased in recent years in the context of various scattering anomalies, their topological properties have not been fully assessed. In this work, it is theoretically and experimentally demonstrated that non‐Hermitian perturbations around bound states in the continuum can lead to singular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 85 publications
0
22
0
Order By: Relevance
“…Fig. 2b shows that the pole and zero possess opposite topological charges, suggesting they could merge if material losses were ignored 34 . Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 2b shows that the pole and zero possess opposite topological charges, suggesting they could merge if material losses were ignored 34 . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the optical response of α-MoO3 bilayers within this frequency range presents an epsilon-near-zero (ENZ) regime, providing exceptional control over light scattering 29,30 . It has been shown that ENZ materials consisting of multiple layers can support embedded eigenstates (EE), also known as bound states in the continuum, with incredibly high Q-factors [31][32][33][34] . All these distinct properties make α-MoO3 particularly compelling for thermal emission engineering applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Topological concepts are essential in explaining and predicting unique phenomena like bound states in the continuum (BIC) also known as an embedded eigenstate. BIC is an eigenmode of an optically open system that exhibits an unbounded radiative Q-factor, even though it lies within the continuum of unbounded states. , BIC can be realized in symmetry-protected scenarios, such as a hedgehog-like arrangement of dipole polarization along a sphere , or over a plane, or by exploiting the destructive interference between at least two strongly coupled resonant modes linked to the same radiation channel. , More recently, the topological scattering features of BIC were discussed in nonperiodic, planar reflective structures using epsilon-near-zero (ENZ) and epsilon-near-pole (ENP) materials, , which was also leveraged in acoustic and nonreciprocal electromagnetic systems . The ENZ resonances are commonly found in isotropic, anisotropic, and 2D materials, such as InAs, ITO, SiC, α-MoO 3 , and hBN.…”
Section: Miscellaneous Topics On Topological Metamaterialsmentioning
confidence: 99%
“…543,1121−1130 BIC can be realized in symmetry-protected scenarios, such as a hedgehoglike arrangement of dipole polarization along a sphere 1122,1124 or over a plane, 1127 or by exploiting the destructive interference between at least two strongly coupled resonant modes linked to the same radiation channel. 1121,1131−1138 More recently, the topological scattering features of BIC were discussed in nonperiodic, planar reflective structures using epsilon-nearzero (ENZ) and epsilon-near-pole (ENP) materials, 1128,1139 which was also leveraged in acoustic 1140 and nonreciprocal electromagnetic systems. 1141 The ENZ resonances are commonly found in isotropic, anisotropic, and 2D materials, such as InAs, ITO, SiC, α-MoO 3 , and hBN.…”
Section: Topological Properties Of Scattering Anomaliesmentioning
confidence: 99%